Políticas linguísticas em um contexto transfronteiriço: representações de professores sobre o Pacto Nacional pelo Fortalecimento do Ensino Médio - PNEM. - Silva, Izabel da (2016)
This research aimed to investigate how the Pacto Nacional pelo Fortalecimento do Ensino Médio - PNEM - is inscribed in language and education policies and what representations the research partners build, locally, on this continuing education in a cross-border school context of the city of Foz do Iguaçu/PR. In order to achieve the proposed objective, I sought to answer two research questions: 1) How language policies, combined with educational policies, historically, have been built in Brazil, among them the PNEM? and 2) What representations of a multidisciplinary group of teachers and pedagogues are evidenced locally through their discursive practices, on the continuing education policy PNEM? The research in question sought to achieve an interface between the theoretical and methodological field of Applied Linguistics (hereinafter LA) and Education (KLEIMAN, 1998; PENNYCOOK, 1998; BAKHTIN (VOLOCHINOV) ([1929] 2006; RAJAGOPALAN, 2006, 2013; etc). Thus, I made a cutout covering Linguistic Policy and Educational Policy in the theoretical foundation of the research (HAMEL, 1993; CALVET, 2002; SHOHAMY, 2006, 2010; SAVIANI, 2008, 2011; JAFFE, 2009; SHIROMA et. al., 2011; MAHER, 2013; among others). So I opted for a methodology of qualitative / interpretative and ethnographic (ERICKSON, 1989; DENZIN & LINCOLN, 2006; FLICK, 2009). The dissertation was organized into three chapters. In the first chapter, I presented the theoretical and methodological approach of the research; I contextualize the linguistic and cultural reality and superdiversity the border region that circumscribes the city of Foz do Iguaçu/PR and the Colégio Estadual Ipê Roxo; as well as the reordering of PNEM locally. The constitution of the corpus consists of: field notes from participant observation of collective meetings at school, during the year 2015; the formation of books I, II and IV of Step 2 of the PNEM and their production activities collective textual; and excerpts from the discursive practices of participants in a focus group. The second chapter has attempted to answer the first research question. The results indicated that with the colonization of Brazil, also undertook a linguistic colonization (MARIANI, 2004); and with it come the first actions of linguistic and educational policies as "Regiments" of D. João III, the Pombaline Reform, with the imposition of the Portuguese language by the Diretório do Índios in 1757 (SOARES, 2008); or, in the twentieth century, the linguistic repression established to immigrants and their descendants, in the government of the Estado Novo; among many others. In Chapter 2, I noted also that different concepts of language were underlying the teaching and language policies of each historical moment in Brazil. The third chapter sought to answer the second research question. The analysis and interpretation of the data showed, among other things, that the parties had representations sometimes contradictory regarding the continuing education of PNEM. For the same time they seemed to assume a position of language policy agents, resisting the top-down policy (SHOHAMY, 2006); at other times, they end up claiming that the training was also conducted for teachers of Ensino Fundamental II. In fact, I realized that the lack of debate in collective meetings, unable by reordering the PNEM locally, made important issues to local realities, such as the linguistic and cultural diversity, were minimally discussed. Furthermore, the analysis of the documents governing the PNEM and Training books, as well as the interpretation of the discursive practices of the interlocutors revealed distinct focus of attention. On the one hand, the representations of the parties on the students of Colégio Estadual Ipê Roxo, proved almost always negatively stereotypical way; with the statement that the diversity of the local reality determines a priori the students learning problems. On the other hand, the documents show greater concern for the rights to student learning, however, did not mention what could be the rights of teachers. Although the contract clearly define as a requirement that the teacher articulates theory and practice in the context of the classroom, the authors of the continuing education of PNEM end up neglecting their methodological part.